2020
DOI: 10.1111/apha.13587
|View full text |Cite
|
Sign up to set email alerts
|

L‐lactate induces neurogenesis in the mouse ventricular‐subventricular zone via the lactate receptor HCA1

Abstract: Aim Adult neurogenesis occurs in two major niches in the brain: the subgranular zone of the hippocampal formation and the ventricular‐subventricular zone. Neurogenesis in both niches is reduced in ageing and neurological disease involving dementia. Exercise can rescue memory by enhancing hippocampal neurogenesis, but whether exercise affects adult neurogenesis in the ventricular‐subventricular zone remains unresolved. Previously, we reported that exercise induces angiogenesis through activation of the lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 110 publications
(137 reference statements)
2
26
0
Order By: Relevance
“…HCAR1 activation led to increased cerebral vascular endothelial growth factor A (VEGFA) expression, a mediator of angiogenesis that is known to improve neurogenesis and cognition [90,117]. The authors found that, similar to high-intensity exercise, subcutaneous injection of L-lactate (to mimic exercise-induced raise in lactate serum levels) leads to higher brain VEGFA levels [116], capillary density [116] and adult neurogenesis [118,119]…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…HCAR1 activation led to increased cerebral vascular endothelial growth factor A (VEGFA) expression, a mediator of angiogenesis that is known to improve neurogenesis and cognition [90,117]. The authors found that, similar to high-intensity exercise, subcutaneous injection of L-lactate (to mimic exercise-induced raise in lactate serum levels) leads to higher brain VEGFA levels [116], capillary density [116] and adult neurogenesis [118,119]…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Furthermore, a follow-up study by Morland and colleagues ( Lambertus et al, 2020 ) demonstrated that exercise had a strong HCAR1-dependent effect on adult neurogenesis in the subventricular zone (SVZ). Using the same HIIT paradigm or injection of L-lactate could activate HCAR1 and promote neurogenesis in SVZ.…”
Section: Main Textmentioning
confidence: 99%
“…There is also controversy about the way lactate affects changes in the brain. Some research results indicate that lactate can activate the PGC1-α/FNDC5/BDNF pathway through SIRT1 or act through NMDA, while some results show it is HCAR1 ( Yang et al, 2014 ; Morland et al, 2017 ; El Hayek et al, 2019 ; Lambertus et al, 2020 ). Even studies reported that lactate promotes choroidal neovascularization by upregulating VEGF expression in macrophages, regardless of the activity of lactate transporter MCT ( Song et al, 2018 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…A role of HCAR1 in cell proliferation was previously shown in cancer and osteoblast cell lines 12,13 . A very recent paper also showed HCAR1 dependent neurogenesis after high intensity physical exercise 43 . Similar to our study, this paper found neurogenesis to be HCAR1 dependent in the subventricular zone, but not in the hippocampus.…”
Section: Discussionmentioning
confidence: 94%